GAMBARAN TINGKAT PENGETAHUAN SWAMEDIKASI OBAT BATUK PADA PASIEN DI APOTEK MARS DEPOK PERIODE JUNI–JULI 2024 : Overview of Knowledge Level of Self-Medication for Cough Among Patients at Apotek X June–July 2024 - Annisa Eka Handayani; Aprilia Fatma Ely; Imam Syafi’i (UIMA Press, 2026)
Self-medication is a self-treatment effort undertaken by the public to treat mild symptoms such as coughs, without consulting a medical professional. Knowledge is an important factor in determining the appropriateness and safety of self-medication, as insufficient knowledge can lead to irrational drug use and health risks. This study aims to determine the level of knowledge and analyze the relationship between this level of knowledge and self-medication behavior of cough medicine among patients at Mars Pharmacy, Depok, from June to July 2024. This study used a quantitative descriptive design with a cross- sectional approach. A sample of 77 respondents was selected using a purposive sampling technique. The instrument used was a closed-ended questionnaire that had been tested for validity and reliability. Data were analyzed univariately and bivariately using the Chi- Square test. The results showed that the majority of respondents had sufficient knowledge (58.4%) and moderate cough self-medication behavior (49.4%). The Chi-Square test results indicated a significant relationship between knowledge and cough self-medication behavior (p = 0.001). There was a significant relationship between knowledge and cough self-medication behavior among patients at Mars Pharmacy, Depok. Improved education and provision of drug information by pharmacists are needed to promote appropriate, safe, and rational self-medication behavior.